PENYALAHGUNAAN NAPZA MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Nurhafizah Nurhafizah; Hasuri Hasuri; Rokilah Rokilah (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2023)
ABSTRACT Drug abuse is pathological use of drugs (outside of treatment) that has lasted for at least one month in a row and causes disruption in social, school or work functioning. The impact of drug abuse in particular is that it can lead to dependence which is difficult to cure, and even drug users tend to increase the dose they consume to meet their needs. This study aims to determine the factors that influence drug abuse and to determine abuse in terms of Law Number 35 of 2009 concerning Narcotics. This research is empirical juridical in nature, namely an approach by looking at a legal reality in society and the method of collecting data in this study is divided into two, namely the library research method and field research methods such as interviews, observation, and documentation. The research results found that the factors that influence drug abuse in the Maja Polsek area are based on the results obtained that the most dominant factors causing drug abuse are personality, association and social or community. The number of drug cases that occurred in the Maja Polsek area was 19 cases and 23 suspects from the beginning of 2022, in terms of the age of suspected drug dealers and users, the productive age dominated, namely 20-29 years, 11 suspects, 10 suspects aged > 30 years and the rest are at the age of 16-19 years.